2020
DOI: 10.1111/hsc.13096
|View full text |Cite
|
Sign up to set email alerts
|

Local drug prevention strategies through the eyes of policy makers and outreach social workers in Norway

Abstract: More than half of the municipalities in Norway report drug misuse as the most important public health challenge. Following a whole‐of‐government tradition, the ambition is to achieve horizontal and vertical coordination between different policy areas to address complex problems, such as youth drug use, and avoid fragmented services. This study aims to offer new perspectives on how governmental structures shape local drug prevention. By including the perspective of both local policy makers and outreach social w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Although acknowledged as an intervention method, the terms “street work” and “outreach” are often used interchangeably ( Andersson, 2013 ; Szeintuch, 2015 ). Social work outreach targets specific populations, including the homeless ( Grymonprez et al, 2020 ; Kydra & Compton, 2009 ; Szeintuch, 2015 ; Ungpakorn & Rae, 2020 ); drug users ( Korf et al, 1999 ; Needle et al, 2004 ; Oldeide et al, 2020 ); sex workers ( Gerassi & Howard, 2018 ; Saldanha & Parenteau, 2013 ); individuals coping with mental illness ( Rowe et al, 2015 ); and unemployed youth ( Andersson & Minas, 2021 ). However, the profession's current emphasis on direct outreach for such vulnerable populations as well as advocacy for coordinated service provision for them is not as strong as it was in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Although acknowledged as an intervention method, the terms “street work” and “outreach” are often used interchangeably ( Andersson, 2013 ; Szeintuch, 2015 ). Social work outreach targets specific populations, including the homeless ( Grymonprez et al, 2020 ; Kydra & Compton, 2009 ; Szeintuch, 2015 ; Ungpakorn & Rae, 2020 ); drug users ( Korf et al, 1999 ; Needle et al, 2004 ; Oldeide et al, 2020 ); sex workers ( Gerassi & Howard, 2018 ; Saldanha & Parenteau, 2013 ); individuals coping with mental illness ( Rowe et al, 2015 ); and unemployed youth ( Andersson & Minas, 2021 ). However, the profession's current emphasis on direct outreach for such vulnerable populations as well as advocacy for coordinated service provision for them is not as strong as it was in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Among the selected policy and service areas shown in Figure 7, health receives the most academic attention in terms of the number of articles. The articles in this category include Agrawal et al (2021) on children's holistic health under India's nurturing care framework for early childhood development; Oldeide et al (2021) on the problem of drug misuse among youths in Norway; and Rochford et al (2021) on suicide prevention in Ireland. A relatively high volume of articles was also published addressing issues of public order and safety, such as Matzopoulos and Myers (2014) on violence prevention in South Africa, as well as issues of defense, such as Brook (2012) on a unified budget for national security in the United States, Brunk (2016) on peacebuilding in fragile states, and Fukushima and Samuels (2018) on Japan's creation of the National Security Council in 2013.…”
Section: Findings and Key Themesmentioning
confidence: 99%
“…The research also alternatively suggests a single organization to play the role of focal organization; for example, Keirstead (2007) proposes stronger leadership be exercised by the UK Department of Trade and Industry in the JUG promotion of microgeneration policies. Other studies suggest that excessive control by these focal organizations is not desirable, and a hybrid control structure ensures flexible and adaptive networking on the ground (e.g., Oldeide et al, 2021). Molenveld et al (2020) collected views of practitioners towards horizontal coordination and reported voices in favor of boundary settings with “room to maneuver” at an organizational level (p. 17).…”
Section: Findings and Key Themesmentioning
confidence: 99%
“…Penggunaan narkoba secara tepat dapat menjadi obat untuk menyembuhkan penyakit dan mengurangi rasa sakit. Meskipun demikian, terdapat pula beberapa orang yang menyalahgunakan narkoba sebagai obat penenang dan penghibur ketika mendapat masalah (Oldeide et al, 2021). Penggunaan narkoba yang salah ini dapat memberikan efek ketergantungan.…”
Section: Pendahuluanunclassified